Empresa bananera e intervención política en Costa Rica (1899-1939) y Honduras (1912- 1933) - García Buchard, Ethel (1997)
Analyses the diverse mechanisms of intervention used by the banana companies to exert pressure and to interfere in the political live in Costa Rica and Honduras during the first decades of the 20 th century.